ACTIVITY OF A TEACHER OF COMPUTER SCIENCES IN AN INSTITUTION OF GENERAL SECONDARY EDUCATION IN THE PARADIGM OF NORMATIVE REQUIREMENTS FOR ITS IMPLEMENTATION - Voda, Anton; Yurchenko, Artem; Ostroha, Mariia (Physical and Mathematical Education, 2022)
The article examines the regulatory framework, according to which the professional activity of informatics teachers in institutions of general secondary education is carried out.Formulation of the problem. Reforming the educational sector often leads to uncertainties or contradictions in the implementation of the educational process, and therefore the regulatory framework on which the activity of each subject in this process is based is important. Given the constant development of information technologies and tools and the need to ensure the appropriate level of training of students in informatics, special attention is needed to the normative basis of the activities of the informatics teacher within the framework of the educational system, the coverage of which became the goal of this article.Materials and methods. Normative base, in the paradigm of which the professional activity of a computer science teacher is carried out. Analysis and systematization to identify and describe the regulatory framework of teacher activity in the legal field of Ukraine; analysis to clarify the requirements for the organization of the work of the computer science office as a place of professional activity of the computer science teacher; comparison of educational and professional programs and the list of learning outcomes and general and special competencies to identify the results of computer science teachers' training by regulatory documents.Results. Systematized regulatory documents that guide informatics teachers in their professional activities.Conclusions. The organization of computer science training in the school is based on the general regulatory and legal basis, official documentation of the computer science office, sanitary and hygienic requirements, safety and occupational health and safety techniques, and educational and methodological support of the computer science office. The requirements for the organization of the work of the computer science office are defined by the Order of the Ministry of Education and Culture "On the Approval of Sanitary Regulations for General Secondary Education Institutions" and the Standard List of Computer Equipment for Preschool, General Secondary and Professional (Vocational-Technical) Education Institutions (Order of the Ministry of Education and Culture of November 2, 2017 No. 1440 as amended from April 27, 2021 No. 458).
Keywords: informatics teacher; the activity of an informatics teacher; regulatory requirements; requirements for the preparation of an informatics teacher; informatics office; educational and methodological support of an informatics office